2003
DOI: 10.1159/000070387
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Route of Reconstruction on Morbidity, Mortality and Local Recurrence after Esophagectomy for Cancer

Abstract: Background: A choice of retrosternal or orthotopic route for reconstruction exists after three-phase esophagectomy with cervical anastomosis. Whether the route of reconstruction affects postoperative morbidity, mortality and recurrence patterns remains controversial. Study Design: Patients with cancer of the thoracic esophagus who underwent three-phase esophagectomy between 1990 and 1999 were studied. Postoperative outcome, recurrence patterns and survival were analyzed from a prospectively collected database.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 9 publications
2
24
0
1
Order By: Relevance
“…One possible explanation for the significant difference in pulmonary complications might be the slightly higher rate of intrathoracic anastomosis in the MIE group and the consequent avoidance of an additional cervical incision with its complications. However, the risk for pulmonary complications and hospital mortality was reported to be independent of the type of reconstruction in a prospective randomized trial comparing neck anastomosis with intrathoracic anastomosis [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…One possible explanation for the significant difference in pulmonary complications might be the slightly higher rate of intrathoracic anastomosis in the MIE group and the consequent avoidance of an additional cervical incision with its complications. However, the risk for pulmonary complications and hospital mortality was reported to be independent of the type of reconstruction in a prospective randomized trial comparing neck anastomosis with intrathoracic anastomosis [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…7 Wong and associates reported that recurrent tumor infiltration of the gastric conduit occurs in 14% of patients when the orthotopic route is used. 16 Katsoulis et al reported that retrosternal interposition can minimize reflux compared with the use of the posterior mediastinal route. Reflux of the contents of the duodenum following posterior mediastinal reconstruction is less severe.…”
Section: Discussionmentioning
confidence: 99%
“…The retrosternal route necessitates the formation of an extra tunnel, leading to additional blood loss13, more cardiopulmonary complications14 and a higher rate of postoperative atelectasis15. In a previous comparison of the results of retrosternal and orthotopic pull‐up of the stomach, there was no significant difference in hospital mortality rates, but tumour relapse was more common after reconstruction involving the orthotopic route13. The retrosternal route might therefore be preferable after incomplete resections (R1 or R2) as irradiation of the tumour bed would not compromise the graft.…”
Section: Discussionmentioning
confidence: 99%